Uncertainty in maritime risk analysis: Extended case study on chemical tanker collisions - Sormunen OVE; Goerlandt F; Hakkinen J; Posti A; Hanninen M; Montewka J; Stahlberg K; Kujala P (SAGE PUBLICATIONS LTD, 2022)
Uncertainty is inherent to risk analysis. Therefore, it is extremely important to properly address the issue of uncertainty. In the field of risk analysis for maritime transportation systems, the effect of uncertainty is rarely discussed or quantified. For this reason, this article discusses a case study dealing with risk analysis for a chemical spill in the Gulf of Finland and analyses the related uncertainties by adopting a systematic framework. Risk is assessed in terms of the expected spill frequency and spill volumes caused by collisions between ships and chemical tankers in the Gulf of Finland. This is done by applying a collision consequence with a novel approach-to-collision-speed linkage model and Gulf of Finland-specific causation factors, which are based on reanalysing accident data. This article also presents a metamodel for assessing collision probability with initial vessel speeds for any given scenario where a chemical tanker is about to be struck by another vessel. Even when conducting a risk analysis using state-of-the-art methods, there is still a medium-high degree of uncertainty in the model presented in this article, which only becomes apparent when conducting a systematic uncertainty assessment analysis. However, an uncertainty assessment is an important part of quantitative maritime risk analysis. For this purpose, a qualitative framework for uncertainty assessment analysis is introduced for general use in the field of maritime risk analysis.